Flow and heat transfer characteristics of supercritical carbon dioxide in mini-channels - Thiwaan Rao, Narasimma Naidu (2018)
Supercritical carbon dioxide (scCO2) is being used in many engineering applications because at supercritical stage, it has unique thermal properties with enhanced heat transfer and flow characteristics. Carbon dioxide (CO2) at supercritical phase is being used recently in Heating, Ventilation, Air Conditioning, and Refrigeration (HVAC&R) industries due to its special thermal properties of supercritical CO2. However, the effects of some process and geometrical parameters on the thermal hydraulic performance of scCO2 are not fully examined. Thus, the aim of this study is to develop single phase flow and heat transfer model and to investigate the effect of some process parameters (inlet pressure, inlet temperature, and inlet flow rate) and geometrical parameters (Tube inner diameter and tube shape) on the performance of scCO2 cooling process. For the numerical investigation, two cases were considered: straight and helical tubes at various tube diameters. The model was developed based on the assumption that the scCO2 flow is incompressible, turbulent and non-isothermal. The developed numerical model was validated using experimental data from open literature for the straight tube and by conducting experiments for the helical tube case. Both the simulation and experiment were performed at various input parameter range: pressure (7.0 MPa – 10 MPa), temperature (35 ºC – 80 ºC), flow rate (10 L/min – 35 L/min) and tube diameter (2.8 mm – 4.5 mm). The model validation results indicated that the average percentage error between the simulation and experimental results were less than 10%. This indicates that the developed model can be used to predict the performance of scCO2 cooling process. Both the experimental and simulation results indicated that the heat transfer coefficient reaches peak value near the pseudo-critical point. Heat transfer coefficient decreased as inlet pressure increased beyond critical point but increased with increasing flow rate. Meanwhile, highest pressure drop value was recorded near the critical point. On the other hand, the smaller the inner tube diameter the higher the heat transfer coefficient will be. The pressure drop in a system decreased when the system inlet pressure is increased but increased with increasing flow rate. Besides, the sensitivity analysis results of Nusselt number and pressure drop indicate that the best input parameters in scCO2 cooling. Inlet pressure with value near critical point, smaller tube ID and higher flow rate could achieve both enhanced heat transfer and low pressure drop at the same time. However, increasing inlet temperature could deteriorate heat transfer rate even though lower pressure drop was attained. These parameter combinations could help reducing the pumping power associated with pressure drop.